2015
DOI: 10.1002/jcph.675
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase Activity and Malondialdehyde Serum Concentrations Remain Unaffected in Response to Hydroxyurea Therapy inβ-Thalassemia Patients

Abstract: β-Thalassemia is the most common hereditary disorder characterized by reduced production of β-globin chains of hemoglobin A (HbA). In recent years, hydroxyurea (HU) has shown promising therapeutic benefits in patients with β-thalassemia by fetal hemoglobin augmentation. We have analyzed effects of hydroxyurea treatment on oxidative stress in β-thalassemia patients by assessing activities of paraoxonase (PON) and arylesterase along with malondialdehyde (MDA) and total reactive oxygen species (ROS) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Serum paraoxonase/arylesterase 1 (PON1) is an antioxidant enzyme carried on HDL that also hydrolyzes lipid peroxidation products in LDL [34]. Decreased activities of PON1 associated with increased oxidative stress, decreased Hb levels, and increased atherosclerosis risk have been reported in thalassemic patients [34][35][36][37]. Curcuminoids cocktail enhances PON1 intensities in correlation with decreased ROS levels, which was consistent with the ELISA results (Figure 2), supporting by a previous in vivo study [38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Serum paraoxonase/arylesterase 1 (PON1) is an antioxidant enzyme carried on HDL that also hydrolyzes lipid peroxidation products in LDL [34]. Decreased activities of PON1 associated with increased oxidative stress, decreased Hb levels, and increased atherosclerosis risk have been reported in thalassemic patients [34][35][36][37]. Curcuminoids cocktail enhances PON1 intensities in correlation with decreased ROS levels, which was consistent with the ELISA results (Figure 2), supporting by a previous in vivo study [38].…”
Section: Discussionsupporting
confidence: 88%
“…Serum paraoxonase/arylesterase 1 (PON1) is an antioxidant enzyme carried on HDL that also hydrolyzes lipid peroxidation products in LDL [34]. Decreased activities of PON1 associated with increased oxidative stress, decreased Hb levels, and increased atherosclerosis risk have been reported in thalassemic patients [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Our further analyses showed that peripheral neuropathy score (TNSn) correlated positively with transfusion frequency and serum ferritin; highlighting an association between severe iron overload and motor neuropathy which was further proved by the regression analysis model. B-thalassemia patients were recently proved to have a higher rate of ROS production with subsequent oxidative stress [17,18]. This may play a role in the pathogenesis of neurological dysfunction [19].…”
Section: Discussionmentioning
confidence: 99%
“…on intracellular anti-oxidant levels, metabolic pathways, handling of trace elements required for enzymes in different metabolic pathways, oxygen binding and dissociation from haemoglobin-F are not entirely known. Our group has previously reported interesting results of proteomics, metallomics, metabolomics and genomics in β-thalassemia patients with and without the institution of HU [9][10][11][12][13]. Primary and secondary genetic modifiers, like beta globin gene mutations and presence or absence of XMN-1, HSB1L-MYB, and BCL-11A polymorphisms, have been found to significantly influence the response of HU in improving haemoglobin levels in beta thalassemia patients [14].…”
mentioning
confidence: 96%
“…One important initial finding was that serum paraoxonase activity and malondialdehyde serum concentrations remain unaffected in response to hydroxyurea therapy in β-thalassemia patients [11]. This implies that HU does not adversely affect metabolic pathways in these patients.…”
mentioning
confidence: 99%